2021
DOI: 10.1155/2021/9567056
|View full text |Cite
|
Sign up to set email alerts
|

Aconitine Induces TRPV2-Mediated Ca2+ Influx through the p38 MAPK Signal and Promotes Cardiomyocyte Apoptosis

Abstract: Aconitine is the main effective component of traditional Chinese medicine Aconitum, which has been proved to have severe cardiovascular toxicity. The toxic effect of aconitine on cardiomyocytes is related to intracellular calcium overload, but the mechanism remains unclear. The aim of this study was to explore the mechanism of aconitine inducing intracellular Ca2+ overload and promoting H9c2 cardiomyocyte apoptosis through transient receptor potential cation channel subfamily V member 2 (TRPV2). After treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Moreover, 21 studies were deleted because the outcome measurement was not of interest. Ultimately, 32 eligible articles ( Liang et al, 1991 ; Meng, 2006 ; Fu, 2007 ; Liu, 2007 ; Wang, 2007 ; Wang et al, 2007 ; Zhang, 2007 ; Xu, 2008 ; Liu, 2009 ; Deng, 2010 ; Fang et al, 2012 ; Zhang et al, 2012 ; Wang, 2013 ; Zhou et al, 2013 ; Sun et al, 2014 ; Yu, 2015 ; Cui et al, 2018 ; Gao, 2018 ; Gao et al, 2018 ; Hu et al, 2018 ; Li et al, 2018 ; Zhang et al, 2018 ; Liu et al, 2019 ; Wang M. et al, 2020 ; Li et al, 2020 ; Peng et al, 2020 ; Zhang et al, 2020 ; Zhou et al, 2020 ; Xia et al, 2021 ; Yang et al, 2021 ; Ye et al, 2021 ; Wang S. et al, 2022 ) were identified for further evaluation, data extraction, and analysis ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, 21 studies were deleted because the outcome measurement was not of interest. Ultimately, 32 eligible articles ( Liang et al, 1991 ; Meng, 2006 ; Fu, 2007 ; Liu, 2007 ; Wang, 2007 ; Wang et al, 2007 ; Zhang, 2007 ; Xu, 2008 ; Liu, 2009 ; Deng, 2010 ; Fang et al, 2012 ; Zhang et al, 2012 ; Wang, 2013 ; Zhou et al, 2013 ; Sun et al, 2014 ; Yu, 2015 ; Cui et al, 2018 ; Gao, 2018 ; Gao et al, 2018 ; Hu et al, 2018 ; Li et al, 2018 ; Zhang et al, 2018 ; Liu et al, 2019 ; Wang M. et al, 2020 ; Li et al, 2020 ; Peng et al, 2020 ; Zhang et al, 2020 ; Zhou et al, 2020 ; Xia et al, 2021 ; Yang et al, 2021 ; Ye et al, 2021 ; Wang S. et al, 2022 ) were identified for further evaluation, data extraction, and analysis ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Of them, the animals used in three studies ( Liang et al, 1991 ; Zhang et al, 2012 ; Sun et al, 2014 ) comprised Sprague–Dawley (SD) and Wistar rats, and two studies ( Deng, 2010 ; Wang, 2013 ) guinea pigs. The weight of rats ranged from 150 to 350 g, and the weight of guinea pigs ranged from 300 to 350 g. Among which, zebrafish embryos were employed in seven studies ( Fang et al, 2012 ; Cui et al, 2018 ; Liu et al, 2019 ; Wang S. et al, 2020 ; Li et al, 2020 ; Xia et al, 2021 ; Ye et al, 2021 ), H9c2 cell in nine studies ( Gao, 2018 ; Gao et al, 2018 ; Hu et al, 2018 ; Zhang et al, 2018 ; Li et al, 2020 ; Peng et al, 2020 ; Zhang et al, 2020 ; Yang et al, 2021 ; Wang W. et al, 2022 ), primary cardiomyocytes of SD rats in 10 studies ( Meng, 2006 ; Fu, 2007 ; Wang, 2007 ; Wang et al, 2007 ; Zhang, 2007 ; Xu, 2008 ; Liu, 2009 ; Zhou et al, 2013 ; Yu, 2015 ; Li et al, 2018 ), primary cardiomyocytes of Wistar rats in three studies ( Liu, 2007 ; Sun et al, 2014 ; Zhou et al, 2020 ). Meanwhile, three studies chose primary cardiomyocytes of guinea pigs ( Wang, 2013 ) and AC-16 cells ( Cui et al, 2018 ; Zhou et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The TRPV1 channel is a thermosensitive channel that can be activated by Aconitum plants and components such as capsaicin and aconitine, which in turn can induce apoptosis, Ca 2+ overload, and so on, leading to a certain degree of toxicity [ 52 – 55 ]. Some literature also suggested that one of the causes of cardiotoxicity of Caowu may also be related to the activation of TRPV1 channel [ 31 , 33 , 34 ]. Meanwhile, our experiments also proved this notion: activation of TRPV1 channel induced by MA could accelerate the generation of apoptosis, decrease the mitochondrial membrane potential, and intracellular Ca 2+ overload, which was significantly reversed by BCTC, a TRPV1 antagonist.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, ion channels are an important way to exert the efficacy and toxicity of diester alkaloids. When the function of ion channels is aberrant, the proportion of each channel in the myocardium will be destroyed, which will induce cardiac diseases such as arrhythmia ( Fu et al, 2007 ; Yang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%